Closed bipolar electrodes for spatial separation of H2 and O2 evolution during water electrolysis and the development of high-voltage fuel cells - Goodwin, Sean; Walsh, Darren A. (American Chemical Society, 2017)
Electrolytic water splitting could potentially provide clean H2 for a future ‘Hydrogen Economy.’ However, as H2 and O2 are produced in close proximity to each other in water electrolysers, mixing of the gases can occur during electrolysis, with potentially dangerous consequences. Herein, we describe an electrochemical water-splitting cell, in which mixing of the electrogenerated gases is impossible. In our cell, separate H2- and O2-evolving cells are connected electrically by a bipolar electrode in contact with an inexpensive dissolved redox couple (K3Fe(CN)6/K4Fe(CN)6). Electrolytic water splitting occurs in tandem with oxidation/reduction of the K3Fe(CN)6/K4Fe(CN) redox couples in the separate compartments, affording completely spatially-separated H2 and O2 evolution. We demonstrate operation of our prototype cell using conventional Pt electrodes for each gas-evolving reaction, as well as using earth-abundant Ni2P electrocatalysts for H2 evolution. Furthermore, we show that our cell can be run in reverse, and operate as a H2 fuel cell, releasing the energy stored in the electrogenerated H2 and O2. We also describe how the absence of an ionically-conducting electrolyte bridging the H2- and O2-electrode compartments makes it possible to develop H2 fuel cells in which the anode and cathode are at different pH values, thereby increasing the voltage above that of conventional fuel cells. The use of our cell design in electrolysers could result in dramatically improved safety during operation, and the generation of higher-purity H2 than available from conventional electrolysis systems. Our cell could also be readily modified for the electrosynthesis of other chemicals, where mixing of the electrochemical products is undesirable.